Sucrose induced hypertriglyceridaemia: its mechanism and metabolic effects - Vrána, A; Fábry, P; Kazdová, L; Poledne, R; Slabochová, Z (Czechoslovak medicine, 1982)
The study summarizes the metabolic effects of increased sucrose or fructose intake. Compared with the traditional carbohydrate source-starch, a high intake of the above two carbohydrates produces a number of metabolic and other changes that can have a pathological effect. A thus induced metabolic and other changes that can have hepatic lipid synthesis, hypertriglyceridaemia and increased tissue lipid utilization, while tissue glucose utilization decreases. Moreover, the increase of these carbohydrates can lead to some pathological organ changes and elevation of blood pressure.
Keywords: intestinální absorpce; Liver; Animals; Intestinal Absorption; játra; Fructose; inbrední kmeny potkanů; Sucrose; triglyceridy; Triglycerides; Rats, Inbred Strains; Insulin; fruktosa; glukosa; Glucose; krysa rodu Rattus; zvířata; Dietary Carbohydrates; inzulin; sacharosa; dietní sacharidy; Rats